"It's a Racist Plot": An Experimental Test of the Racial Defense. Issue 5 (September 2022) - Crawford, Nyron N.
Black municipal leaders are routinely accused of using race and racism to sidestep allegations that they have run afoul the ethics of public office. That is, they use racial defenses to respond to what they view as racist attacks against them. This type of race-based account has been treated as commonplace in American politics, but its effectiveness as a political account has received little scholarly attention. For example, how effective is the racial defense at minimizing negative political fallout for scandalized Black politicians? Using data from a survey experiment, I test how Black Americans respond to the political accounts profferred by Black elected officials accused of official misconduct. I show that a strategy involving a racial defense can yield positive evaluations in terms of trait judgment and voter intention, while offering no comment reduces participant suspicion about investigative malfeasance.